Some interpretations on FTIR results for the detection of Ganoderma boninense in oil palm tissue - Arnnyitte Alexander; Jedol Dayou; Coswald Stephen Sipaut @ Mohd Nasri; Lee, Ping Chin (e-VIBS, Faculty of Science and Natural Resources, 2014)
The use of Fourier Transform Infrared (FTIR) spectroscopy has been employed for the past three decades in the study of biological samples and characterization of biomolecules. Objective: In this paper, the author have conducted the feasibility study of detecting Ganoderma boninense in infected oil palm tree using Fourier transform infrared spectroscopy (FTIR). Results: It was found that result from FTIR plot is capable of showing the presence of Ganoderma boninense with good sensitivity. Conclusion: In this paper, the mechanisms behind this detection are discussed. This is due to the unique functional groups that exist in the Ganoderma boninense which cannot be found in healthy oil palm tissue.